Diagnostic accuracy of metagenomic next-generation sequencing for cryptococcosis in immunocompetent and immunocompromised patients - Su, Yi; Miao, Qing; Li, Na; Hu, Bi-jie; Pan, Jue (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract Objective: To compare the diagnostic accuracy of metagenomic next-generation sequencing (mNGS) for cryptococcosis in patients with different immune statuses with that of conventional detection. Methods: A total of 1442 samplespecimens including 71 samplespecimens from cryptococcosis patientspatients with cryptococcosis were analyzed in the study. The chi square test was used to screen the sensitivity and specificity of different detection methods for different samplespecimen types. One-way ANOVA was used to compare the mNGS results with the laboratory indexes One-way ANOVA was used to compare the mNGS results with age, CD4, lymphocytes, IFN, IL-6, IL-2 and serum antigen assay. Results: The sensitivity of mNGS was 44.29% in cryptococcusCryptococcus infection cases. The positive rate of mNGS results for bronchoalveolar lavage fluid (BALF, 87.50%) from immunocompromised patients was higher than that of BALF from immunocompetent patients (40.00%, p=0.04). The sensitivity of the serum cryptococcusCryptococcus capsular antigen assay was 80.00% in immunocompetent patients and 96.42% in immunocompromised patients (p = 0.049). In immunocompromised patients, Aa positive ratepositive of detection of Cryptococcus from mNGS result was positively correlated with higher when cryptococcal antigen ≥1:160 (p=0.022) in immunocompromised patients. A positive rate of detection of Cryptococcus from mNGS was higher when lymphocyte counts were lower in both immunocompetent patients(p=0.017) and in immunocompromised patients(p=0.029). Positive mNGS results were negatively correlated with lymphocyte counts. Conclusions: The sensitivity of mNGS is lower than that of serum cryptococcal antigen assay and histopathology in immunocompetent patients that of traditional detection methods. However, BALF detection is recommend for immunocompromised patients compared with other types of samplesfor immunocompromised patients compared with tissue and CSF. The positive mNGS result was negatively correlated with lowerthe lymphocyte counts, higher IL-2 and higher serum antigen assay in immunocompromised patients.